Taxonomic value of leaf anatomical characteristics in Lepisanthes (Roxb.) Leenh. (Sapindaceae) of Peninsular Malaysia - Mohd Norfaizal Ghazalli,; Noraini Talip,; Abdul Latiff, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Taxonomic value of leaf anatomical characteristics in Lepisanthes (Roxb.) Leenh. (Sapindaceae) of Peninsular Malaysia. Leaf anatomical study was carried out on five species of Lepisanthes (Roxb.) Leenh. (Sapindaceae), namely L. amoena, L. fruticosa, L. rubiginosa, L. senegalensis, and L. tetraphylla. The studies involved a cross-section method using sliding microtome on petioles, lamina, midribs, and leaf margins, leaf clearing method and leaf epidermis mechanical scrapping, and light microscope observation. The objective was to observe the taxonomic value of the leaf anatomical features. The results showed that there are three common generic features, nine features whose variations can be used for species differentiation, and three diagnostic features that can be used for species identification. The common generic features consist of the presence of a layer of collenchyma cells in the petioles and the presence of cells or mucilaginous canals in the midribs. The anatomical features with variations consist of features of outer shape and pattern of petiolar vascular tissue, outer shape and vascular tissue of midribs, leaf margin shape, presence of brachysclereid cells, and leaf venation type. The results showed that the anatomical features of leaves in Lepisanthes have taxonomic value, especially in species differentiation and recognition.